ESP Students' Demotivation In Learning English: A Study Of An Islamic Education Study Program - Risa Arroyyani; Ika Sulis Setianingsih; Dhian Marita Sari (Journal on Education, 2024)
In learning English, motivation is an important factor that can support the success of the English language learning. This research aims to explore the factors that demotivate students in learning English, involving 37 students of Islamic education. Employing a descriptive design with both quantitative and qualitative data, this study indicated that the factors causing student demotivation in learning English came from both internal and external factors. The internal factors were such as students' lack of motivation to learn English which led to a lack of improvement and practice, difficulty in studying English, and their low self-determination and self-confidence which affected their proficiency. For external factors, this study indicated that teacher-related factors significantly influence student motivation, including ineffective teaching styles and methods and lack of attention to students' personal needs by teachers. Internal factors are also related to the learning environment, where students feel demotivated due to a lack of learning facilities, limited interaction, and boring classmates.